Degradasi Biksin Selama Pemanasan dan Pencahayaan - Ardiyanto Pranata; Sri Raharjo; Umar Santoso; Haryadi Haryadi (agriTECH, 2006)
The kinetics of thermal and light induced degradation of natural bixin in a mixture of ethanol and 2 % acetic acid (80 : 20) was studied as a function of temperatures 80, 98, and 125 OC for 120 minutes. Illumination was carried out either under fluorescent or incandescent lights, both at 4000 lux for 300 minutes. The bixin concentration during heating and illumination was analysed using HPLC. The method to determine the degradation rate constant for the decay of the products from bixin was obtained using a linear regression according to first order reaction.  The results indicated that the degradation rates of bixin at 125 OC were 5.5 and 3.8 times faster than that of 80 OC and 98 OC, respectively. The energy activation of bixin was 9.82 kcal/mol. The photodegradation rate constants of bixin under incandescent or fluorescent illumination was 2.8 x 10-3 and 3.3 x 10-3 minutes-l, respectively.